Relationship between frailty in older adults and decreased grip strength - Peralta Vargas, Carmen Eliana (2022)
Objective: To find out if decreased grip strength is associated with frailty and adverse outcomes at three-month follow-up. Materials and methods: A descriptive, observational and prospective study. Patients older than 59 years of age attending a day hospital were included in the research. The dominant hand grip strength was measured during an outpatient visit. Frailty was assessed using the Edmonton Frail Scale. The association between decreased grip strength, frailty and adverse outcomes at three-month follow-up was evaluated using the chi-square test and Student’s t-test.Results: Grip strength was measured in 82 older adults (out of whom 46 were females) whose mean age was 83.68 years. Based on the Edmonton Frail Scale, 83.33 % of the study subjects were severely frail, 87.87 % were moderately frail, 86.66 % were mildly frail and 46.66 % were vulnerable to frailty. According to this scale, “not frail” older adults were those who did not show decreased grip strength. Decreased grip strength was associated with frailty (p = 0.002). Adverse outcomes at three-month follow-up were frequent in older adults with decreased grip strength (p = 0.49) and those with frailty (p = 0.48), although such outcomes were not statistically significant. Conclusions: Decreased grip strength is associated with frailty. At three-month follow-up, all the study participants who died had decreased grip strength.